PENGARUH PROSES DUA TAHAP DAN PELARUT DALAM PENCAIRAN BATUBARA - Priyanto, Unggul (Jurnal Energi dan Lingkungan (Enerlink), 2006)
The influence of solvent was examined in the single- and two-stageliquefaction of Tanito Harum coal with FeNi supported oil carbon black(FeNi/KB) and a synthetic pyrite. FeNi/KB catalyst provide a high oi l yield inthe single-stage liquefaction when tetralin or 1methylnapthalene wasused, while pyrite (FeS2) gave a low oil yield in the liquefaction with 1-methylnapthalene although it produced a high enough oil yield in theliquefaction with tetralin. The single-stake liquefaction of coal gave extremelylow oil yields under the solvent free conditions for all catalysts examined. Inthe liquefaction of coal with solvent, the difference of oil yield producedbetween single-stage and two stage is small. However, the conversion of H–donor solvent after liquefaction was much lower than that of single-stageliquefaction. In the free-solvent liquefaction coal, two-stage liquefactionproduced much higher oil yield than single-stage.Kata kunci: solvent, catalyst, single-stage coal liquefaction, two-stage coalLiquefaction